CREATION AND DEVELOPMENT OF TEACHER PROFESSIONAL LEARNING COMMUNITY: INSTITUTIONAL FACTORS - Monkevicius, Justinas; Čiužas, Renaldas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article presents a theoretical and empirical analysis of institutional factors of creation and development of successful teacher professional learning communities. On the basis of the conducted theoretical analysis, institutional factors were systemised and divided into four groups:factors related to organisational culture, to processes, to organisational structure, and factors related to financial and material resources.The empirical research reveals the relevance of theoretically distinguished factors to the practical processes of creation and development of successful teacher professional learning communities. It also singles out new factors that have not been investigated by other scholars and highlights the encountered barriers.